2017
DOI: 10.1080/00194506.2017.1333464
|View full text |Cite
|
Sign up to set email alerts
|

Drying of Almonds I: Single Particle

Abstract: Drying is an essential unit operation required in food processing industries, particularly in the dry fruits industry. Drying of almonds exhibit many characteristic features such as non-spherical shape, swelling/ shrinkage as a function of moisture content, uneven drying because of their peculiar shape and proximity to other almond kernels and so on. In this study, we have investigated the drying of almonds through experiments and computational modeling. In this regard, Mettler Toledo Halogen moisture analyzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…It is therefore essential to develop fully coupled model equations for flow, temperature, moisture variation and solids temperature representing processes occurring in a tray dryer which need to be solved simultaneously. Based on our earlier work for single and multiple particles (Chilka and Ranade [9,10] ), it showed that temperature equilibrium within the almond particle was achieved quickly. The Biot number for heat transfer and mass transfer for almonds is 0.17 and 2.1, respectively.…”
Section: Modelling Of Flow Heat Transfer and Drying In A Tray Dryermentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore essential to develop fully coupled model equations for flow, temperature, moisture variation and solids temperature representing processes occurring in a tray dryer which need to be solved simultaneously. Based on our earlier work for single and multiple particles (Chilka and Ranade [9,10] ), it showed that temperature equilibrium within the almond particle was achieved quickly. The Biot number for heat transfer and mass transfer for almonds is 0.17 and 2.1, respectively.…”
Section: Modelling Of Flow Heat Transfer and Drying In A Tray Dryermentioning
confidence: 99%
“…Based on the single particle work, the effective diffusivity of an almond kernel was estimated, as reported by Chilka and Ranade . As for tray drying, there could be a temperature variation in the unit, hence diffusivity needs to be estimated at respective air temperatures.…”
Section: Modelling Of Flow Heat Transfer and Drying In A Tray Dryermentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed CFD models were developed to simulate flow and heat transfer within the unit and across all the particles. Influence of neighboring almond particles on heat and mass transfer coefficients was quantified by comparing the results with the single particle results from earlier work [3] . This presented experimental data, approach and models will be useful to understand the drying kinetics of almonds in different drying units.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work was carried out for drying of a single almond kernel [3] to identify suitable drying kinetics model for almonds, estimation of heat transfer coefficient, mass transfer coefficient and effective diffusivity. The moisture variation for single almond during the drying process was predicted using simulations which matched quite well with experimental measurements.…”
Section: Introductionmentioning
confidence: 99%